Worldwide Acquisition by Indian Companies: A Case Study of HINDALCO Industries Ltd - Pandey, Shishir; Shankar, Uma (Indian Journal of Finance, 2008)
During the last few months, most of the Indian companies were indulge in acquisition activities to explore the contemporary practices of corporate community in order to stay competitive. The acquisition of US - Canadian aluminium company 'Novelis' by India based company 'HINDALCO Industries Limited (HINDALCO)', a part of Aditya Vikram Birla Group of Companies, in 2007, is one of them, which makes the HINDALCO, the word's largest aluminium rolled products producer as well as Asia's largest primary aluminium producer.The present study discusses the acquisition of Novelis by HINDALCO and explains the acquisition deal in detail as well as highlights the benefits of the deal for both the companies. It also examines the challenges that HINDALCO would face in integrating the operations of Novelis.